Surface activity of concrete waste powders - Arkady M. Ayzenshtadt; Tatiana A. Drozdyuk; Victor E. Danilov; Maria A. Frolova; Georgiy A. Garamov (Нанотехнологии в строительстве, 2021)
: Introduction. One of the most large-tonnage wastes of the construction industry is a concrete scrap, obtained as a result of the dismantling of buildings and structures, the service life of which has reached its maximum or requires significant capital changes. In our opinion, works on the use of the resulting dust-like fraction are of particular interest. One of the promising methodological approaches in this direction is the observance of the principles of nanotechnology, which consists of obtaining finely dispersed components as active components of the created compositions. Materials and methods. Therefore, the objects of research in this work were fine powders obtained by mechanical grinding of lightweight (sample 1) and heavy (sample 2) concrete of a five-story residential panel house built in 1979. The elemental composition and specific surface area of the samples were determined, thermogravimetry of the studied powder systems was carried out, the surface tension of the experimental samples and the dispersion and polarization components of this indicator were determined by the OVRK method. A new methodological approach to the determination of the surface tension of powder systems is proposed, based on the determination of the functional dependence of the surface tension on the pressing force of the prototypes. The possibility of calculating macroenergy characteristics (atomization energy, specific mass atomization energy) of waste concrete samples is shown. These physicochemical indicators characterize the potential supply of internal energy of the system, which is capable of transforming into free surface energy during mechanical destruction of the material. Results and discussions. Thermogravimetric analysis of experimental concrete samples showed the presence of a residual amount of belite. Calculations of the surface activity of the samples showed that it is more preferable to use a powder obtained by crushing a sample of heavy concrete as an active additive in compositions capable of exhibiting the properties of a binding agent. Conclusions. To assess the activity of dusty fractions of concrete scrap as a component in binding compositions of the hydration type of hardening, it is proposed to use the value of the surface activity of powder systems as a criterion. The absolute numeric value of this criterion is equal to the ratio of the values of the free surface energy of the investigated powder and the specific mass energy of atomization of the initial waste concrete. It was found that for concrete waste the value of this criterion is determined by the polarization component of surface tension.